Enhancing Eleventh Grade Students’ TOEFL Listening Ability through Socialization Activities at SMK Nusantara Tanah Jawa - Miranda Kristin Lumban Tungkup; Esra Delima Hutabarat; Sarah Priscilla Silitonga; Vercelly Hot Taruli Manik; Calvyn Sepanya Siregar; Yanti Kristina Sinaga; Herman Herman; Marto Silalahi (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study presents a socialization activity that introduced the Test of English as a Foreign Language (TOEFL) to 11th-grade students in the TKJ program at SMK Nusantara Tanah Jawa. This initiative aimed to raise awareness of the TOEFL test format, its importance, and its relevance to academic and career development. A qualitative descriptive approach was used, involving 16 students through a structured program consisting of preparation, implementation, and evaluation stages. Findings indicated that most students were initially unfamiliar with the TOEFL, especially the listening component. However, this socialization activity effectively increased students' understanding and interest in English learning, especially in the listening section. Challenges such as low prior knowledge and limited engagement were addressed through simplified explanations and interactive sessions. Overall, the activity contributed positively to improving students' English language competence and motivation, preparing them to understand the TOEFL listening section for global academic and professional demands.